INTERORGANIZATIONAL RELATIONS AUTO PARTS INDUSTRY: THE CASE OF TENANT FIRMS - Kardoyo, Hadi; Laksani, Chichi Shintia (Journal of S&T Policy and R&D Management, 2013)
Inter Organizational relations (IOR) plays an important role in enhancing firms activities. By utilizing IOR, firms may acquire knowledge, access to economic inputs, and build their competitive advantages. Meanwhile, automotive industry which is characterized by high degree of vertical interdepencies generally retain a well developed and great varieties of IOR.This paper aims to analyze IOR in IndonesiaÃ¢â¬â¢s automotive industry by conducting case studies of three Japanese firm tenants. The result of the study shows that IOR occured in those three companies. Nevertheless, the IOR differs among the tenants in terms of types, causal factors, driving factors, and barriers. These variations depend on the firmÃ¢â¬â¢s position within the industrial structures developed by Japanese automotive manufacturers. The closer the firmÃ¢â¬â¢s position, the stronger the IOR. The study also identifies that IOR in the second layer firms contribute to the firmÃ¢â¬â¢s learning activities and their technological capabilities.